Psychological analysis of aggressive behavior of prisoners - Sergei Zavadsky (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
This article analyzes the aggressive behavior of prisoners in conditions of social isolation. The analysis of the causes and factors that determine the appearance and manifestation of aggressive behavior of prisoners is considered.
Keywords: adaptation; aggressive behavior; environmentof prisoners; prison status; correction; behavior; conflict